Effect of EPEC endotoxin and bifidobacteria on intestinal barrier function through modulation of toll-like receptor 2 and toll-like receptor 4 expression in intestinal epithelial cell-18 - Yang, Xia (World J Gastroenterol, 2017)
AIM: To investigate toll-like receptor 2 (TLR2) and TLR4 expression, following bifidobacteria and low-dose EPEC endotoxin treatment, and intestinal barrier function in rat intestinal epithelial cell18 (IEC18). METHODS: Six experimental groups were established - normal control, EPEC, Bifidobacteria infantis (B. infantis), B. longum, B. bifidum, and B. youth groups. Optimal EPEC endotoxin concentration, bifidobacteria fold dilution, and treatment duration were determined. Quantitative real-time polymerase chain reaction and western blot, respectively, were conducted to detect TLR2 and TLR4 mRNA and protein expression in IEC-18 cells. Transepithelial electrical resistance (TEER) was measured by the EVOM chopstick voltohmmeter in each group. All experiments were conducted in triplicate and data were analyzed on SPSS 16. RESULTS: TLR2 and TLR4 mRNA and protein expression in the EPEC group were significantly higher than in the control group (P < 0.05). TLR2 mRNA and protein expression in the B. infantis, B. longum and B. youth groups were significantly lower than in the normal control group (P < 0.05). TLR4 mRNA and protein expression in the B. bifidum and B. youth groups were significantly lower than in normal controls (P < 0.05). In addition, the TEER in B. infantis, B. longum, B. bifidum, and B. youth groups were decreased by 19%, 18%, 23% and 23%, respectively, after 120 min of intervention, as compared to the control group. However, the TEER in the EPEC group was significantly decreased by 67% in comparison to the normal control group (P < 0.05). CONCLUSION: Bifidobacteria protect IEC-18 cells against injury by down-regulating TLR2 and TLR4 expression and enhance intestinal barrier function to protect the intestinal epithelial cells from pathogenic invasion.